Discussion of "Honor Among Thieves: Open Internal Reporting and Managerial Collusion"1. (19th September 2016) - Glover, Jonathan; Kim, Eunhee
Abstract: Evans, Moser, Newman, and Stikeleather (2016) use experiments of a one‐shot game to analyze the impact of open versus closed internal reporting on collusive managerial behavior. They interpret their results as inconsistent with economic theory. To better contrast their findings with economic theory and to expand their view of same, we sketch economic models capable of explaining many aspects of their results. We also critique the research design and offer an alternative payoff structure. We then relate their experiments to the seminal research of Berg, Dickhout, and McCabe (1995) on trust and reciprocity. Finally, we provide suggestions for further research.